REFORMULATING POLICY ON FREQUENCY USAGE FEES AS NON-TAX STATE REVENUE: URGENCY AND ITS IMPLICATIONS - Rosdiana, Haula (Journal of Indonesian Economy and Business, 2010)
Spectrum/frequency is a backbone of telecommunication industry and an input to produce various goods and services. Because of its being a limited resource, by tradition it has come to be owned by the state. Many governments levy usage fees/charges to establish a managed spectrum environment or to generate national fiscal income. This varies in different countries. Government of Indonesia levies several taxes and fees/charges totelecommunication operators. As a result, there are double or multi-tax costs of taxation, which can distort productivity. This phenomenon shows that government should considerreformulating frequency usage fees policy in order to minimize the cost of taxation, promote teledencity, affordability, and growth of telecommunication industry. Moreover, many researches have showed that telecommunication industry could accelerate GrossNational Product (GNP).This study describes all taxes and fees/charges applied to telecommunication industry in Indonesia, comparing them to those of some other countries, and analyze frequencyusage fees based on the theory of earmarking tax. An alternative way to reformulate levy policy on frequency usage fee is analyzed by simulating its impacts using system dynamic.The result shows that taxes and fees/charges applied to telecommunication industry increased cost of taxation, and government should simplify in order to give them moreopportunity to increase their productivity resulting in products of good quality and affordable price. Furthermore, it is better for government to levy frequency usage feesbased on earmarking concept, so the frequency regulator can optimize its role to manage spectrum effectively and efficiently. Moreover, the government can provide public anduniversal services, especially in rural areas.Keywords: Frequency Fees, Earmarked Tax, Cost of Taxation, Supply side tax policy